Assessment of functionality and scientific evidence of mobile health applications (mHealth apps) for people with dementia and their caregivers - Zeiler, Michael; Chmelirsch, Christina; Kolominsky-Rabas, Peter (EUROPEAN PSYCHIATRY, 2022)
CRIS-Team WoS Importer:2023-03-17

A User-Centered Design Approach for a Screening App for People With Cognitive Impairment (digiDEM-SCREEN): Development and Usability Study - Zeiler, Michael; Dietzel, Nikolas; Haug, Fabian; Haug, Julian; Kammerer, Klaus; Pryss, Rüdiger; Heuschmann, Peter; Grässel, Elmar; Kolominsky-Rabas, Peter; Prokosch, Hans-Ulrich (JMIR Human Factors, 2025)
Background: Dementia is a widespread syndrome that currently affects more than 55 million people worldwide. Digital screening instruments are one way to increase diagnosis rates. Developing an app for older adults presents several challenges, both technical and social. In order to make the app user-friendly, feedback from potential future end users is crucial during this development process. Objective: This study aimed to establish a user-centered design process for the development of digiDEM-SCREEN, a user-friendly app to support early identification of persons with slight symptoms of dementia. Methods: This research used qualitative and quantitative methods and involved 3 key stakeholder groups: the digiDEM research team, the software development team, and the target user group (older adults ≥65 years with and without cognitive impairments). The development of the screening app was based on an already existing and scientifically analyzed screening test (Self-Administered Tasks Uncovering Risk of Neurodegeneration; SATURN). An initial prototype was developed based on the recommendations for mobile health apps and the teams’ experiences. The prototype was tested in several iterations by various end users and continuously improved. The app’s usability was evaluated using the System Usability Scale (SUS), and verbal feedback by the end users was obtained using the think-aloud method. Results: The translation process during test development took linguistic and cultural aspects into account. The texts were also adapted to the German-speaking context. Additional instructions were developed and supplemented. The test was administered using different randomization options to minimize learning effects. digiDEM-SCREEN was developed as a tablet and smartphone app. In the first focus group discussion, the developers identified and corrected the most significant criticism in the next version. Based on the iterative improvement process, only minor issues needed to be addressed after the final focus group discussion. The SUS score increased with each version (score of 72.5 for V1 vs 82.4 for V2), while the verbal feedback from end users also improved. Conclusions: The development of digiDEM-SCREEN serves as an excellent example of the importance of involving experts and potential end users in the design and development process of health apps. Close collaboration with end users leads to products that not only meet current standards but also address the actual needs and expectations of users. This is also a crucial step toward promoting broader adoption of such digital tools. This research highlights the significance of a user-centered design approach, allowing content, text, and design to be optimally tailored to the needs of the target audience. From these findings, it can be concluded that future projects in the field of health apps would also benefit from a similar approach.
CRIS-Team Scopus Importer:2025-02-14
Keywords: aging; cognitive disorder; cognitive impairment; dementia; design; development; digiDEM; feedback; mHealth; mobile app; mobile health; older adults; screening; usability; user centred; user-centered

Digital screening tool for the assessment of cognitive impairment in unsupervised setting - DigiDEM-SCREEN: Study protocol for a validation study - Zeiler, Michael; Dietzel, Nikolas; Kammerer, Klaus; Frick, Ulrich; Pryss, Rüdiger; Heuschmann, Peter; Prokosch, Hans-Ulrich; Grässel, Elmar; Kolominsky-Rabas, Peter (BMJ Open, 2025)
Introduction Dementia is one of the most relevant widespread diseases, with a prevalence of currently 55 million people with dementia worldwide. However, about 60-75% of people with dementia have not yet received a formal diagnosis. Asymptomatic screening of cognitive impairments using neuropsychiatric tests has been proven to efficiently enhance diagnosis rates. Digital screening tools, in particular, provide the advantage of being accessible without spatial or time restrictions. The study aims to validate a digital cognitive screening test (digiDEM-SCREEN) as an app in the German language. Methods and analysis This is a multicentre study in Bavaria. Participants are people with mild cognitive impairment, people with dementia in an early stage and cognitively healthy people. Recruitment will take place in specialised diagnostic facilities (memory outpatient clinics). 135 participants are aimed based on a power analysis. Sociodemographic data, diagnosis and results of neuropsychiatric tests (Consortium to Establish a Registry for Alzheimer's Disease, Montreal Cognitive Assessment, digiDEM-SCREEN) will be collected at one point per person via electronic data capturing. The sensitivity, specificity and corresponding cut-off values will be determined based on receiver-operating-characteristic curves. The correlation of the digiDEM-SCREEN test with existing cognitive screening/testing procedures will be analysed. Ethics and dissemination The study obtained ethical approval from the Ethics Committee of the Julius-Maximilians-Universität of Würzburg (JMU) (application number: 177/23-sc). The test will give feedback about the current cognitive status and possible cognitive impairments that should lead to the users seeking further diagnostic measures by medical professionals. It will be accessible free of charge in established app stores. The results of the validation study will be published in peer-reviewed journals.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chronic Disease; Cognition; Dementia; eHealth; GERIATRIC MEDICINE

Evaluation of a Digital Dementia Registry's IT Architecture After a Three-Year Period in Practice: digiDEM Bayern - Zeiler, Michael; Dietzel, Nikolas; Kolominsky-Rabas, Peter; Grässel, Elmar; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2024)
INTRODUCTION: The project "digiDEM Bayern" aims to set up a registry with long-term follow-up data on people with dementia and their family caregivers. For that purpose an Electronic Data Capture (EDC) system linked with a Participant Management (PM) system has been established. This study evaluates the acceptance and usability of the IT tools supporting all data management processes in order to further improve the system and associated processes. METHODS: For this purpose we collected the key numbers of the registry, and used the System Usability Scale (SUS) to evaluate the interactions of the data management systems in a wide area. RESULTS: Thirty-six research partners (RP) and six study team (ST) members completed the anonymous online survey. The EDC system overall reached an average SUS score of 73.42 and the PM system of 77.92. DISCUSSION: The two systems fulfil their required task and, therefore, simplify the work of the RP in the data collection process and of the ST during the data quality checks. CONCLUSION: Integrating the used systems is therefore recommended for registry studies in other medical areas.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Dementia; Evaluation; IT Architecture; Online Survey; Registry

Wissenschaftliche Evidenz und Nutzerqualität von Mobile-Health-Anwendungen für Menschen mit kognitiven Beeinträchtigungen und deren Angehörige - Zeiler, Michael; Chmelirsch, Christina; Dietzel, Nikolas; Kolominsky-Rabas, Peter (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2023)
Introduction: The range of health-related apps is large, but the scientific evidence for them is uncertain. The aim of this study is to evaluate the methodological quality of German-language mobile health apps for people with dementia and their caregivers. Methods: The app search was conducted according to the PRISMA-P guidelines in the application stores (Google Play Store and Apple App Store) using the terms “Demenz”, “Alzheimer”, “Kognition” and “Kognitive Beeinträchtigung”. A systematic literature search with subsequent assessment of the scientific evidence was performed. The user quality assessment was conducted using “The German Version of the Mobile App Rating Scale” (MARS-G). Results: Scientific studies have been published for only 6 of the 20 apps identified. A total of 13 studies were included in the evaluation, whereby the app itself was the subject of investigation in only two publications. In addition, methodological weaknesses were often observed such as small group sizes, short study duration and / or insufficient comparative treatment. The overall quality of the apps can be rated as acceptable with a mean MARS rating of 3.38. Seven apps were able to achieve a score of over 4.0 and thus a good rating, but just as many apps fell below the acceptable limit of 3.0. Discussion: The contents of most apps have not been scientifically tested. This identified lack of evidence is consistent with the information in the literature in other indication areas. A systematic and transparent evaluation of health applications is necessary to protect end-users and better support their selection process.
CRIS-Team Scopus Importer:2023-04-14
Keywords: App; Dementia; Evaluation; Evidence; mHealth